Ultraestructura y ontogenia de un tendón digital en tres especies de anuros - Vera, Miriam Corina (2019)
Tendons are biomechanical systems of force transmission and movement of the skeleton. Because of their biomechanical uniqueness, tendons and collagen fibrils have been studied in many groups of vertebrates. Studies on the ultrastructure and ontogeny of the tendon of anurans are practically non-existent. The aim of this study was to analyze the development of collagen fibrils of the flexor tendon of the digit IV of the hand of three anuran species in larval, juvenile and adult stages. In larval and juveniles stages the diameter is homogeneous; in adults, fibrils increment their diameter but also smaller fibrils are observed, consequently it shows a distribution with a bimodal tendency. This developmental pattern was also found in mammals, and was associated to different functions of the tendon. We also found interspecific differences in the fibrils diameter, suggesting an allometric pattern that could be associated to the different mechanical demands acting on the tendons of these species.